Seasonal Fluctuations and Vertical Heterogeneity of Biochemical–Structural Parameters in Wetland Emergent Aquatic Vegetation - Huaijing Wang; Yunmei Li; Jianguang Wen; Gaolun Wang; Huaiqing Liu; Heng Lyu (Plant Phenomics)
Accurate understanding of vertical patterns of canopy structure characteristics and solar radiation distribution patterns of aquatic vegetation is pivotal in formulating a bidirectional reflection model and comprehending the ecological dynamics of wetlands. Further, physiological and biochemical stratified structural properties of aquatic vegetation in wetlands remain unexplored due to more inherent investigation challenges than terrestrial vegetation. This study evaluated the structural characteristics of vegetation communities and the regulation of direct solar radiation variations within the canopy across seasons of Phragmites australis (P. australis) and Typha orientalis (T. orientalis), 2 typical emergent aquatic vegetations (EAVs), based on radiative transfer theory. Observations revealed that physiological and biochemical metrics varied at different growth stages with canopy height, the stratified leaf area index in the middle being higher than at the top and bottom of the P. australis cluster. Moreover, the vertical profiles of direct solar radiation decrease with depth, showing a bowl-shaped and V-shaped curve in the P. australis and T. orientalis clusters, respectively. Interestingly, the sensitivity of layered solar direct radiation transmittance to canopy structural parameters is obviously higher than that of canopy pigments, suggesting considerable potential for estimating layered structural parameters. The transmittance of direct solar radiation decreases with increasing leaf area index at different heights, and stratified transmittance in the cluster can be accurately described by a negative binomial function with a deviation of less than 2%.